Analysis of the Impact of Industrialisation on the Green Economy Development in Malaysia Using STIRPAT Model - Au Yong, Hui Nee (Malaysian Journal of Business and Economics (MJBE), 2018)
The objective of this study is to investigate the impact on carbon emission by applying Regression on Population, Affluence and Technology (STIRPAT) in Malaysia over the period of 1970 – 2013. After testing using the unit root test, cointegration approach was applied to examine the cointegration relationship between the variables. Cointegration results indicate a co-movement between variables in the long-run. The results from the Granger causality test show that the urban population unidirectional causality influences carbon emission. On the other hand, the urban population together with industry have also a unidirectional causality towards gross domestic product. Furthermore, the regression results show that urban population is the significant cause of an increase in carbon emission. Based on the results, the study offers some directions to reduce the carbon emission and provides policy reference for the development of green economy. The government should consider these when constructing long-term strategies for carbon abatement. Keywords: carbon emission, energy consumption, green economy, industrialisation, urbanisation